Cyclical Earnings, Career and Employment Transitions - Carlos Carrillo-Tudela; Ludo Visschers; David Wiczer (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the cyclical behaviour of earnings risk and career changes. We document that the procyclical skewness of the earnings growth distribution arises mostly from the earnings changes of employer and occupation switchers. To uncover their relative importance in driving cyclical earnings changes and whether this arises from changes in the returns to mobility or mobility shocks, we propose a multi-sector business cycle model with on-the-job search and endogenous occupational mobility. Idiosyncratic occupational mobility is the main driver of cyclical earnings risk, mainly due to cyclical shifts in the returns to this mobility. This is the main reason why the sullying effects of recessions are long-lasting. These effects manifest themselves through a collapse of the job ladder and forgone lifetime earnings gains, especially for low-paid workers, and through large lifetime earnings losses among high-paid workers who experience forced occupational mobility and poor re-employment outcomes.
Keywords: E24; E30; J62; J63; J64; 330; earnings; unemployment; business cycle; search; occupational mobility